Wastewater containing 1,2-Dihydro-2,2,4-Trimethylquinoleyn treated by electrolysis and respirometric method - Inazaki, Thelma Helena [UNESP]; Moraes, Peterson Bueno de; Regis, Gisela [UNESP]; Lopes, Paulo Renato Matos [UNESP]; Montagnolli, Renato Nallin [UNESP]; Pião, Antonio Carlos Simões [UNESP]; Bidoia, Ederio Dino [UNESP] (OMICS International, 2010)
The electrolytic treatment of a real industrial effl uent and simulated wastewater containing the 1,2-dihydro- 2,2,4-trimethylquinoleyn compound (Naugard Q®) had been investigated in order to improve the wastewater biodegradability. The electrolysis was carried out in a batch electrolytic cell using 70TiO2 /30RuO2 electrodes (DSA® anode). After electrochemical treatment, wastewaters were evaluated in terms of Naugard Q® concentration, UV-visible spectrophotometry and biodegradation. Further analyses were conducted in simulated wastewater by gas chromatography and the biodegradation process was monitored using respirometric fl asks. Both real effl uent and simulated wastewater presented a decrease in Naugard Q® concentration. The simulated wastewater electrolytic treatment provided concentration reduction of Naugard Q® about 52.04% after 60 min, whereas real effl uent concentration was reduced by 62.60% after 40 minutes. Furthermore, UV-visible spectra and gas chromatograms presented signifi cant alterations in molecular structure of the compound. After 30 min electrolysis, an increase in simulated wastewater biodegradation was observed. In real effl uent, the biodegradation response was faster, as more CO2 was produced in assays that underwent 10 and 25 minutes of electrolytic treatment. This result is probably related to modifi cations in Naugard Q® molecular structure. It was concluded that the electrolytic treatment followed by bioremediation could be an alternate treatment to degrade this compound.
Keywords: Naugard Q®; Industrial effluent; DSA electrodes; Biodegradation; Water treatment